Pengembangan Lembar Kerja Siswa Menggunakan Pendekatan Saintifik Untuk Meningkatkan Keterampilan Berfikir Kritis Siswa Kelas V Sekolah Dasar - Suryaman, Suryaman; Ningsih, Fitria (UNIB Press, 2021)
The purpose of this research to produce student worksheets scientific based on the demands of the 2013 curriculum to improve the critical thinking skills of elementary school V students on thematic learning worthy of use in the learning process. This type of research is research and development. The data collection techniques conducted by researchers is a poll and a test. This research findings in the form of learning media is a scientific-based student worksheet. Based on the validation results of the media expert, the percentage of eligibility gained as much as 94%. Results obtained from validation by the material members as much as 95%. The results of the student response poll as much as 97%. Based on the results of the pretests the average critical thinking skill of 35, in the postest result of an average score of 96.66. While the N-gain score increased critical thinking skills of 0.95 with the category high. Thus, it can be concluded that the students' critical thinking skills have increased based on five critical thinking skills.